Rekonstruksi Pemikiran Pendidikan Agama Islam sebagai Landasan Pembaruan Sistem Pendidikan - Iskandar Mirza; Akhmad Rozikin; Eden Abdul Manan (Yayasan Al-Afif, 2026)
The rapid development of science, digital technology, globalization, and social change demands a renewal of the education system that is more adaptive to the needs of the times. In this context, Islamic Religious Education (PAI) is no longer sufficient to be understood as a normative process of transmitting religious knowledge, but must be reconstructed into an educational paradigm capable of integrating the spiritual, intellectual, moral, and social dimensions of students. This study aims to analyze the urgency of reconstructing Islamic Religious Education thought as a foundation for educational system renewal and to formulate its development direction in facing 21st-century challenges. The research employs a qualitative approach with a library research method. Data were obtained from relevant scientific literature and analyzed using content analysis techniques. The findings indicate that the reconstruction of Islamic Religious Education thought needs to be directed toward an integrative, transformative, and contextual paradigm that eliminates the dichotomy between religious and general knowledge. This reconstruction includes reform of epistemology, curriculum, learning methods, educator competence, and the utilization of digital technology. Thus, Islamic Religious Education can serve as a foundation for building a humanistic, inclusive education system oriented toward shaping students with noble character and global competitiveness.